2020
DOI: 10.1177/0363546520935867
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Predictors of Subsequent Surgery After Anterior Cruciate Ligament Reconstruction: A 6-Year Follow-up Study

Abstract: Background: The cause of subsequent surgery after anterior cruciate ligament (ACL) reconstruction varies, but if risk factors for specific subsequent surgical procedures can be identified, we can better understand which patients are at greatest risk. Purpose: To report the incidence and types of subsequent surgery that occurred in a cohort of patients 6 years after their index ACL reconstruction and to identify which variables were associated with the incidence of patients undergoing subsequent surgery after t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…In contrast, a history of previous knee surgery and female sex may be more important risk factors for developing arthrofibrosis following ACL reconstruction. Both factors were associated with a 1.8 times higher risk of a reoperation for arthrofibrosis, and this finding is consistent with previous literature [4–6, 17, 26, 27]. A transtibial drilling technique was also associated with a higher risk of arthrofibrosis; however, the reason for this association is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, a history of previous knee surgery and female sex may be more important risk factors for developing arthrofibrosis following ACL reconstruction. Both factors were associated with a 1.8 times higher risk of a reoperation for arthrofibrosis, and this finding is consistent with previous literature [4–6, 17, 26, 27]. A transtibial drilling technique was also associated with a higher risk of arthrofibrosis; however, the reason for this association is unclear.…”
Section: Discussionsupporting
confidence: 90%
“…Further surgery for meniscal tears following ACL reconstruction has also been reported to be as high as 12% [ 18 ]. Other reasons for re-intervention may include complications such as infection, stiffness or hardware irritation.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Paterno et al [15] showed that 21% of young patients who have ACL reconstruction, subsequently have a contralateral ACL injury. Further surgery for meniscal tears following ACL reconstruction has also been reported to be as high as 12% [18]. Other reasons for re-intervention may include complications such as infection, stiffness or hardware irritation.…”
Section: Introductionmentioning
confidence: 99%
“…The rates of rerupture after anterior cruciate ligament reconstruction are of the order of 1.7 to 10.3% when considering studies with a minimum 3-year follow-up in cases of semitendinosus/gracilis tendons autograft (ST/G). 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 Although mispositioning of bone tunnels is the primary cause of anterior cruciate ligament (ACL) reconstruction rerupture by positive or negative anisometry ranging from 52.2% to 95.6%, 9 , 10 , 11 , 12 , 13 the number of risk factors for rerupture are clearly identified in the literature, including genu varum, posterior tibial slope, anterior tibial subluxation and intercondylar notch size. 14 , 15 , 16 , 17 , 18 While data on muscle recovery and return-to-sport (RTS) are very well documented.…”
Section: Introductionmentioning
confidence: 99%